(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the association between self-perceived oral health and oral health status and socioeconomic-demographic factors in quilombola elderly people. Material and methods: This is a cross-sectional study carried out with 47 elderly quilombolas. Dependent variable of self-perceived oral health. The independent variables were the socioeconomic-demographic and oral health variables. The Chi-square or Fisher’s Exact Test, Mann-Whitney and Poisson Regression with robust variance were performed, all with a significance level of 5%. Results: The average age of the elderly was 71 years (SD = ± 7.55). Bivariate analysis of the association of self-perceived oral health with marital status (p = 0.020) and the need to use a prosthesis (p = 0.003). A multivariate analysis using Poisson regression informing the significance for the variable need to use a prosthesis (p <0.0001), therefore, elderly people with a need for a prosthesis prevalence of negative self-perception of oral health 52.3% higher (PR = 1,523; 95%CI = 0.109 - 0.612), when compared to those without the need for a prosthesis. Conclusion: According to the findings of the study, the use of prosthesis seems to benefit from a positive self-perception of oral health in elderly quilombolas.